2020
DOI: 10.1021/jacs.9b13782
|View full text |Cite
|
Sign up to set email alerts
|

Fluidic Multivalent Membrane Nanointerface Enables Synergetic Enrichment of Circulating Tumor Cells with High Efficiency and Viability

Abstract: The ubiquitous biomembrane interface, with its dynamic lateral fluidity, allows membrane-bound components to rearrange and localize for high-affinity multivalent ligand–receptor interactions in diverse life activities. Inspired by this, we herein engineered a fluidic multivalent nanointerface by decorating a microfluidic chip with aptamer-functionalized leukocyte membrane nanovesicles for high-performance isolation of circulating tumor cells (CTCs). This fluidic biomimetic nanointerface with active recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 41 publications
1
122
0
Order By: Relevance
“…[13][14][15] Several groups have demonstrated the engineering of multivalent aptamer for a lower dissociation constant, giving rise to highly efficient CTCs capture. [16][17][18][19][20][21] As a recent example, one study has taken advantage of DNA framework to control the spatial organization of trivalent aptamers against EpCAM (epithelial cell adhesion molecule). Such topological engineering not only merely increases the ligand binding affinity with the membrane receptors, but also prevents the aptamer from endocytosis by cells, which has been evaluated by improved CTCs capture.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Several groups have demonstrated the engineering of multivalent aptamer for a lower dissociation constant, giving rise to highly efficient CTCs capture. [16][17][18][19][20][21] As a recent example, one study has taken advantage of DNA framework to control the spatial organization of trivalent aptamers against EpCAM (epithelial cell adhesion molecule). Such topological engineering not only merely increases the ligand binding affinity with the membrane receptors, but also prevents the aptamer from endocytosis by cells, which has been evaluated by improved CTCs capture.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon strongly suggested that the targeting effect of the nanoparticle was mediated by aCD47. Additionally, aCD47‐conjugated NPs showed significantly higher binding affinity to 4T1 cells in comparison with free aCD47 due to the multivalent effect of NP‐based systems, [ 27–28,34 ] which was demonstrated by the values of the dissociation constant ( K D ) (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] Through interaction with the low‐density lipoprotein receptor‐related protein 1 (LRP1) on macrophages, CALR acts as an “eat me” signal to promote macrophage engulfment of tumor cells. [ 26–28 ] The expression level of CALR is a key determinant of the effectiveness of CD47‐SIRPα axis blockade. [ 29–30 ] When the surface exposure of CALR is low, blockade of CD47‐SIRPα may not elicit sufficient phagocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…A recent emerging novel engineering strategy is the fabrication of biomimetic nanoparticles that combine synthetic nanomaterials with natural biomaterials, such as the membranes of leukocytes (43), RBCs (44) and platelets (45). A fluidic and multivalent engineered nanointerface decorating a microfluidic chip with aptamer-functionalized leukocyte membrane nanovesicles has been described (46). Platelet-leukocyte hybrid membrane-coated magnetic nanoparticles were designed with cell membranes modified with anti-EpCAM for the high-performance isolation of CTCs (45).…”
Section: Application Of Nanomaterials For Isolation and Detection Ofmentioning
confidence: 99%
“…The combination of nanoparticles and cell membranes significantly decreases the nonspecific adsorption and scavenging probability of nanoparticles (45). In addition, placing a layer of soft yet flexible nanovesicles between the cell and capture substrate, which serves as a cushion, can minimize cell damage resulting from interfacial collision (46). Application of microfluidics technology for isolation and detection of CTCs.…”
Section: Application Of Nanomaterials For Isolation and Detection Ofmentioning
confidence: 99%